Does It Even Work? A Theoretical and Practical Evaluation of the War Powers Resolution. Issue 2 (4th May 2017) - Haas, Peter
ABSTRACT: The War Powers Resolution of 1973 represents a policy that attempts to fill a procedural gap in the Constitution, that is, a clear process by which the use of military force is authorized. Based on what is arguably a misinterpretation of the Constitution, it fails to achieve its objective: to constrain the president's discretion in employing military force unilaterally. This article addresses the WPR in four sections. First, it examines the law's theoretical underpinnings. Next, it summarizes the law's provisions, its application, and several direct and indirect approaches that have been applied in studying the use of military force and the WPR. Third, using quantitative analysis, the article seeks to answer three basic questions: 1) Has the WPR had any effect on the U.S. president's decision to employ military force? 2) Has the WPR had any effect on the magnitude of force employed in a conflict? 3) Has the WPR had any effect on the duration of conflicts in which the president has employed military force? Findings indicate that the War Powers Resolution is not a significant factor in presidents' decisions to use military force. Once the president decides to employ force in a given scenario, it also fails to be a significant factor in affecting the magnitude of force that is used. It appears that the law may have an effect on the duration of conflicts involving the U.S. military, but weaknesses in the statistical model leave this question open to further research to confirm or deny this verdict.